A tool to minimize the need of Monte Carlo ray tracing code for 3D finite volume modelling of a standard parabolic trough collector receiver under a realistic solar flux profile. Issue 9 (27th June 2020) - Islam, Majedul; Saha, Suvash C.; Yarlagadda, Prasad K. D. V.; Karim, Azharul
Abstract: The energy collection element of a parabolic trough collector includes a selective coated metallic receiver tube inside an evacuated glass tube. Perpendicularly incident sun light on the parabolic trough mirror aperture is concentrated on the receiver tube highly nonuniformly along its circular direction. This solar energy is collected as thermal energy circulating a suitable heat transfer fluid (HTF) through the tube. This conjugate heat transfer phenomenon under nonuniform heat flux boundary condition is computationally studied applying 3D finite volume (FV) modelling technique of computational fluid dynamics coupled with Monte Carlo ray tracing (MCRT) optical data. The MCRT model simulates the actual flux profile around the receiver tube. Apart from a FV model, this coupled study requires expertise in, and access to, a suitable MCRT code. A combination of polynomial correlations and user‐defined function (UDF) is introduced in this article in order to minimize the need of MCRT codes from subsequent FV modelling of the receiver tube of the Luz Solar 2 (LS2) collector. The correlations are developed from a verified 3D MCRT model, which is equivalent to the local irradiation data as a function of receiver circular location. The UDF includes two algorithms: one to develop solar flux profile from the correlations around the receiver, and the other to calculate heat loss from the receiver. Interpreting the UDF into ANSYS Fluent, a 3D FV model of the LS2 receiver is developed and validated with experimental results. The effectiveness of the UDF as an alternative to MCRT code is verified. The FV model is capable to investigate the heat transfer characteristics of the LS2 collector receiver at different solar irradiation level, optical properties of the collector components, glass tube conditions, HTFs, inserts or swirl generators, collector length, and internal diameter of the tube. Abstract : In order to minimize the need of a Monte Carlo ray‐tracing (MCRT) code for finite volume (FV) modelling of the receiver of Luz Solar II (LS2) collector for realistic nonuniform solar flux profile, polynomial correlations to calculate local irradiation as a function of angular location of the receiver tube were developed using a 3D MCRT model. A user‐defined function (UDF) that includes an algorithm to calculate and populate the solar flux data around the wall boundary of the collector receiver using the correlations and heat loss functions is developed. Interpreting the UDF in the ANSYS Fluent software package, a 3D finite volume (FV) model of the receiver tube is developed and validated for conjugate heat transfer analysis under realistic solar flux profile. The FV model with the UDF as built‐in function has the capacity to adapt a range of variations in daily solar radiation, optical properties of collector components, optical errors and loss factors, heat transfer fluids and flow conditions, collector length and receiver internal designs, glass tube conditions, and environment conditions without a MCRT code as detailed in the article.